Occupational licensing and occupational mobility - Osborne Jackson (Federal Reserve Bank of Boston, 2023)
This paper estimates the impact of occupational licensing at the extensive margin (existence) and intensive margin (qualifications) on the occupational mobility of US workers. Using 2015-2022 Current Population Survey data on worker occupational choices matched to licensing-policy data, I show that the existence of licensing regulation significantly reduces the probability that a worker enters an occupation. This reduced mobility is largely due to licensing fees and minimum thresholds for age and education. This finding may help explain the weak relationship between licensure and product market quality, as binding licensing qualifications likely have mixed links to worker skills.
Keywords: J63; J24; 330; Occupations; licensing; mobility; Current Population Survey